Sharing Economy Platforms A Casebook for Understanding Multiplayers in Sharing Economy Platforms - Yuan, Ruizhi; Liu, Martin J. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
XVII, 206 p. 5 illus., 3 illus. in color.